Desenvolvimento inicial de mudas de euterpe ssp. Após a aplicação de herbicidas - Queiroz, Juliana Roberta Gobi [UNESP]; Junior, Antonio Carlos Da Silva [UNESP]; Pereira, Maria Renata Rocha; Martins, Dagoberto [UNESP] (FapUNIFESP (SciELO), 2016)
Knowledge regarding the use of herbicides in palms fruit is almost nonexistent. Thus, the objective of this work was to evaluate the initial development of seedlings on Euterpeoleraceae and Euterpeedulis. Studies were conducted in two seasons (February 2013 and January 2014) for each species in a completely randomized design with four replications. The treatments tested were: fluazifop-p-butyl (93,8 g ha-1), sethoxydim (184 g ha-1), quizalofop-p-ethyl (75 g ha-1), (clethodim + fenoxaprop-p-ethyl) (50 + 50 g ha-1), fomesafen (225 g ha-1), lactofen (168 g ha-1), nicosulfuron (50 g ha-1), MSMA (1.422 g ha-1), and a control without herbicide. Spraying was performed over seedlings with 45-50 cm tall. Visual evaluations of phytotoxicity, plant height at 7, 14, 21, 28, 35, 42 e 49 days after spraying (DAS) and at the end of the dry mass of shoot.Visual observations showed that all herbicides were selective to the two palm species studied. Some visual injury symptoms eventually noticed (maximum 14%), dissipated of these occurred over time 49 DAS. Analysis of the height and dry mass accumulation of plants showed that E. oleracea palm presented more tolerant to herbicides when compared to E. edulis.All the herbicides can be recommended to the E. oleracea. As to E.edulis, only the herbicidessethoxydim(184 g ha-1), nicosulfuron (50 g ha-1)and mixing clethodim + fenoxaprop-p-ethyl(50 + 50 g ha-1) they did not affect the initial development of seedlings in the two years of study.
Herbicide selectivity in Euterpe spp.
Keywords: Açaí; Juçara; Palm heart; Phytotoxicity